Nihonjinron and depictions of racial foreigners: reporting on black people in Asahi Shimbun (2001–2010). Issue 1 (1st December 2021) - Tajima, Atsushi; Thornton, Michael C.
Abstract : We examine the Japanese-language newspaper Asahi Shimbun for its reporting on Black people in Japan and the United States from 2001–2010, a time when Japan was forced to boost immigration. While a response to major labor shortages, increased diversity required Japan to rethink its relationship with racial others, among whom Blacks have long been unique in Japanese history. While the newspaper's narratives in stories of Japan and the United States had overlapping themes, the emphasis differed with national context. Its reporting on the U.S. characterized Black-Japanese relations as being racially aligned, suggesting Japanese have a parallel set of experiences with Western racism; reporting also described the U.S. failing miserably in its treatment of African Americans. Reporting on Blacks in Japan used black cultural artifacts as a tool to understand Japanese life. On occasion, the "Ambiguous Foreigner" appears when referencing Afro-Japanese families or Africans in Japan. The idea of Japanese racism holds little credence in reporting, but when evident a remedy was quickly and responsively provided. Asahi bolsters the idea of Japanese exceptionalism/ Nihonjinron identity vis-a-vis the U.S. and portrays Japan as a model of a modern, post-racist nation.